2023
DOI: 10.1001/jamanetworkopen.2023.9126
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events of Cannabidiol Use in Patients With Epilepsy

Abstract: ImportanceEpilepsy is one of the most common neurologic disorders globally. Cannabidiol (CBD) has been approved for the treatment of epilepsy, but its use has been associated with several different adverse events (AEs).ObjectiveTo investigate the frequency and risk of AEs developing in patients with epilepsy who are using CBD.Data SourcesPubMed, Scopus, Web of Science, and Google Scholar were searched for relevant studies published from database inception up to August 4, 2022. The search strategy included a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…The side effects are derived from the increase in the concentrations of the clobazam metabolite, N-desmethyl clobazam, through the inhibition of CYP2C19 by CBD, thus intensifying its effects. [ 29 , 32 ] Elevations in liver enzymes are noted, especially in children taking valproic acid, which is associated with worsening seizures and blood dyscrasias, with possible effects on cognitive development. [ 14 ] The interaction between valproic acid and CBD generates transient metabolic stress in the liver in patients who suspend treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The side effects are derived from the increase in the concentrations of the clobazam metabolite, N-desmethyl clobazam, through the inhibition of CYP2C19 by CBD, thus intensifying its effects. [ 29 , 32 ] Elevations in liver enzymes are noted, especially in children taking valproic acid, which is associated with worsening seizures and blood dyscrasias, with possible effects on cognitive development. [ 14 ] The interaction between valproic acid and CBD generates transient metabolic stress in the liver in patients who suspend treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with placebo, CBD was more likely to cause diarrhea, insomnia, rash, decreased appetite, and elevated aminotransferase levels ( p < 0.05). 68 …”
Section: Discussionmentioning
confidence: 99%
“…Compared with placebo, CBD was more likely to cause diarrhea, insomnia, rash, decreased appetite, and elevated aminotransferase levels (p < 0.05). 68 Concomitant ASMs A retrospective study found that the combination of CLB and CBD may have superior efficacy. 67 In contrast, another retrospective study and some prospective studies did not find a difference in efficacy with or without the combination of CLB.…”
Section: Dosagementioning
confidence: 99%
“…It can be assumed that the rise in N-CLB levels is not entirely responsible for the antiseizure activity of CBD. Therefore, the possibility of a pharmacodynamic synergistic interaction between CBD and clobazam cannot be excluded [6,7,10].…”
Section: Pharmacokinetic Interactions Between Cbd and Clobazam And St...mentioning
confidence: 99%
“…While CBD has been reported to exhibit clear-cut antiseizure properties, contradictory pro-and anticonvulsant effects have been observed for THC. The advantageous anticonvulsant efficacy confirmed in numerous studies and their meta-analyses prompted the US Food and Drug Administration (FDA) and European Medicines Agency (EMA) to approve a highly purified CBD formulation for the supportive treatment of seizures related to Dravet syndrome (DS), Lennox-Gastaut syndrome (LGS), and tuberous sclerosis complex (TSC) in patients at least 2 years old [4][5][6][7][8][9][10][11][12]. Both exogenous (from Cannabis sativa) and endogenous cannabinoids, their metabolizing enzymes, like fatty acid amide hydrolase, and cannabinoid receptors form the endocannabinoid system (ECS).…”
Section: Introductionmentioning
confidence: 99%